License to Kill?—Disease Eradication Programs May Not be in Line with the Convention on Biological Diversity. Issue 1 (30th June 2017) - Hochkirch, Axel; Beninde, Joscha; Fischer, Marietta; Krahner, André; Lindemann, Cosima; Matenaar, Daniela; Rohde, Katja; Wagner, Norman; Wesch, Charlotte; Wirtz, Sarah; Zink, Andreas; Lötters, Stefan; et al.
Abstract: Global human population growth is associated with many problems, such as food and water provision, political conflicts, spread of diseases, and environmental destruction. The mitigation of these problems is mirrored in several global conventions and programs, some of which, however, are conflicting. Here, we discuss the conflicts between biodiversity conservation and disease eradication. Numerous health programs aim at eradicating pathogens, and many focus on the eradication of vectors, such as mosquitos or other parasites. As a case study, we focus on the "Pan African Tsetse and Trypanosomiasis Eradication Campaign, " which aims at eradicating a pathogen ( Trypanosoma ) as well as its vector, the entire group of tsetse flies (Glossinidae). As the distribution of tsetse flies largely overlaps with the African hotspots of freshwater biodiversity, we argue for a strong consideration of environmental issues when applying vector control measures, especially the aerial applications of insecticides. Furthermore, we want to stimulate discussions on the value of species and whether full eradication of a pathogen or vector is justified at all. Finally, we call for a stronger harmonization of international conventions. Proper environmental impact assessments need to be conducted before control or eradication programs are carried out to minimize negative effects on biodiversity.